Polyunsaturated Fatty Acid Impact on Clinical Outcomes in Acute Coronary Syndrome Patients With Dyslipidemia: Subanalysis of HIJ‐PROPER. Issue 16 (20th August 2019) - Arashi, Hiroyuki; Yamaguchi, Junichi; Kawada‐Watanabe, Erisa; Koyanagi, Ryo; Sekiguchi, Haruki; Mori, Fumiaki; Haruta, Shoji; Ishii, Yasuhiro; Murasaki, Satoshi; Suzuki, Kazuhito; Yamauchi, Takao; Ogawa, Hiroshi; et al.
Abstract : Background: This study aimed to examine the impact of baseline eicosapentaenoic acid (EPA) to arachidonic acid (AA) ratio on clinical outcomes of patients with acute coronary syndrome. Methods and Results: In the HIJ‐PROPER (Heart Institute of Japan Proper Level of Lipid Lowering With Pitavastatin and Ezetimibe in Acute Coronary Syndrome) study, 1734 patients with acute coronary syndrome and dyslipidemia were randomly assigned to pitavastatin+ezetimibe therapy or pitavastatin monotherapy. We divided the patients into 2 groups based on EPA/AA ratio on admission (cutoff 0.34 μg/mL as median of baseline EPA/AA ratio) and examined their clinical outcomes. The primary end point comprised all‐cause death, nonfatal myocardial infarction, nonfatal stroke, unstable angina pectoris, or ischemia‐driven revascularization. Percentage reduction of low‐density lipoprotein cholesterol and triglyceride from baseline to follow‐up was similar regardless of baseline EPA/AA ratio. Despite the mean low‐density lipoprotein cholesterol level during follow‐up being similar between the low‐ and high‐EPA/AA groups, the mean triglyceride levels during follow‐up were significantly higher in the low‐ than in the high‐EPA/AA group. After 3 years of follow‐up, the cumulative incidence of the primary end point in patients with low EPA/AA was 27.2% in the pitavastatin+ezetimibe group compared with 36.6% in the pitavastatin‐monotherapy group (hazard ratio 0.69; 95% CI, 0.52‐0.93; P =0.015). However, there was no effect of pitavastatin+ezetimibe therapy on the primary end point in patients with high EPA/AA (hazard ratio 0.92; 95% CI, 0.70‐1.20; P =0.52). Conclusions: Among acute coronary syndrome patients who have dyslipidemia and low EPA/AA ratio, adding ezetimibe to statin decreases the risk of cardiovascular events compared with statin monotherapy. Clinical Trial Registration: URL: http://www.umin.ac.jp/ctr . Unique identifier: UMIN000002742